Myo18b is essential for sarcomere assembly in fast skeletal muscle. (20th January 2017) - Berger, Joachim; Berger, Silke; Li, Mei; Currie, Peter D.
Abstract: Congenital myopathies are muscle degenerative disorders with a broad clinical spectrum. A number of myopathies have been associated with molecular defects within sarcomeres, the force-generating component of the muscle cell. Whereas the highly regular organization of the myofibril has been studied in detail, in vivo assembly of sarcomeres remains a poorly understood process. Therefore, a more detailed knowledge of sarcomere assembly is crucial to better understand the pathogenic mechanisms within myopathies. Recently, mutations in myosin XVIIIB ( MYO18B ) have been associated with cases of myopathies, although the underlying mechanism for the resulting pathology remains to be defined. To analyze the role of myosin XVIIIB in skeletal muscle disease, zebrafish mutants for myo18b were generated. Full loss of myo18b function results in a complete lack of sarcomeric structure, revealing a highly surprising and essential role for myo18b in sarcomere assembly. Importantly, scattered thin and thick filaments assemble throughout the sarcoplasm; but fail to organize into recognizable sarcomeric structures in myo18b null mutants. In myo18b partial loss-of-function mutants sarcomeric structures are assembled, but thin and thick filaments remain misaligned within these structures. These observations suggest a novel model of sarcomere assembly where Myo18b coordinates the integration of preformed thick and thin filaments into the sarcomere. Disruption of this highly coordinated process results in a block in sarcomere biogenesis and the onset of myopathic pathology.